Archivo José E. Miguens - Miguens, José Enrique (Universidad de San Andrés, Biblioteca Max von Buch, Colecciones Especiales y Archivos, 2003)
Contains public opinion research material compiled 1958-1973 (bulk 1967-1971) in Argentina under the direction of Dr. José E. Miguens. Includes data on public attitudes regarding privatization, international conflicts, border disputes, political parties, armed forces, social institutions, and other topics.